Optimal power flow based on fuzzy linear programming and modified Jaya algorithms - Alzihaymee, Warid Sayel Warid (2017)
Optimal power flow (OPF) solution is a crucial tool in electric power networks operation. Recently, several factors, including the deregulated electricity markets, electricity consumption growth, the growing role of decision makers, and the increasing exploitation of distributed generation (DG), affect the operation strategies of many meshed power networks. These new conditions have raised the intricacy of OPF problems and necessitate a reliable optimization algorithm that can tackle economic and security concerns.